AB0440 Ethnic minorities experience infrequent biologic switch despite active rheumatoid arthritis disease. (12th June 2018) - Kerr, G.; ,; Swearingen, C.; Hochberg, S.; Ude, J.; Yazici, Y.; ,
Abstract : Background: The expanded therapeutic modalities in rheumatoid arthritis (RA) provide options to achieve low disease activity or remission. Yet, in routine care, the frequency and choice of switching of biologic DMARD (bDMARD) amongst ethnic subsets when there is inefficacy, is unknown. Objectives: To evaluate frequency and choice of biologic switch in ethnic RA subsets Methods: Patients enrolled in the Ethnic Minority RA Consortium (EMRAC), with at least one followup visit were analysed. Data included clinical outcomes as assessed by RAPID3 tender/swollen joint counts; medication use (prednisone, methotrexate, other DMARD), and bDMARD (Tumour Necrosis factor inhibitors (TNFi) and non-TNFi). Minimally clinical improvement (MCI) in RAPID3 was defined as a decrease of ≥3.2 points during followup. Differences between medication usage, biologic switch, and RAPID3 improvement between race and ethnicity groups while on biologics, was investigated. Results: 1040 subjects with 3719 follow-up visits spanning an average of 63.2 weeks were analysed. African Americans and Hispanics comprised 24% and 15%, respectively. Compared to Whites, African Americans and Hispanics had significantly less education (p<0.001 for both), significantly less biologic use (p<0.001 for both) and significantly less TNF use (p<0.001 for both). African Americans had significantly higher RAPID3 scores at enrollment than Whites as well (p=0.018). Switching between TNFi and non-TNFi was recorded in only 9 subjects, with 7 subjects switching from TNFi to non-TNFi. There was no statistical difference between race/ethnic groups in frequency of bDMARD switching, nor within bDMARD class (TNFi class, p=cc; non-TNFi class, p=bb). bDMARD treatment led to MCI in RAPID3 in 101 (38%) subjects and in more African Americans (29 [48%]) and Hispanics (12 [41%]) than in Whites (49 [37%]) (but not statistically significant). Conclusions: In our cohort, disparity was seen in bDMARD use between race and ethnic groups but had similar and infrequent biologic switch. Based upon these data, efforts to eliminate biologic use disparity remains paramount and supersedes concerns regarding disparity in biologic switching. Disclosure of Interest: G. Kerr Grant/research support from: BMS, Genentech, Pfizer, C. Swearingen Grant/research support from: BMS, Genentech, Pfizer, S. Hochberg: None declared, J. Ude: None declared, Y. Yazici Grant/research support from: BMS, Genentech, Pfizer